ANALISIS PENYEBAB KETIDAKSESUAIAN PADA SAMPEL PENGUJIAN KUALITAS PRODUK CAT TEMBOK MENGGUNAKAN FAULT TREE ANALYSIS DI PT. XYZ - Culatta, Vigna Shindy; Rosid, Ibnu Abdul (Jurnal Mitra Teknik Industri, 2024)
Product quality is one of the essential factors in the growth of a company's business. A company that focuses on quality continuously builds consumer trust in the company. Consumers can assess a company based on the products it produces. If a product is of high quality, it means that the company's processes have successfully met quality standards. Therefore, satisfied consumers will be happy to use the product consistently. PT XYZ is one such company that prioritizes quality. Product quality is monitored from the beginning to the end of the production process by the Quality Control department to ensure that the products meet standards. In reality, even when a product goes through the production process according to the correct instructions and formulas, there are still instances of non-conformities found in product samples during quality testing. Therefore, this research aims to analyze the factors causing these issues using the Fault Tree Analysis (FTA) method. The research focuses on wall paint products in the Finish Goods section. By using a Pareto diagram, it was determined that the most common non-conformities were viscosity issues, accounting for 58 instances or 39%, and pH issues, accounting for 51 instances or 34%. Subsequently, an analysis of the causes was conducted using Fault Tree Analysis (FTA), leading to the identification of factors contributing to these failures, including operator factors, process factors, environmental factors, and raw materials.